2015
DOI: 10.1089/pho.2015.3893
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Radiomodulatory Effect of Low-Level Laser Irradiation by Clonogenic Survival Assay

Abstract: Objective: The aim of this study was to investigate the radiomoulatory effects of low-level laser irradiation (LLLI) in normal and cancer cells exposed to ionizing X-ray radiation on clonogenic survival assay. Background data: LLLI does have radioprotective effects on normal tissue. LLLI can reduce the incidence of mucocutaneous complications of ionizing radiation. Few in vitro studies reported adaptive responses for LLLI to ionizing radiation in normal and cancer cells, particularly with respect to clonogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Further studies should be performed to address these issues. LLLT may also selectively inhibit cancer cell proliferation (64) or enhance tumor cell killing with RT (63). This imply that LLLT may have a role as an adjuvant to RT to enhance cancer treatment and be incorporated into the RT treatment plan.…”
Section: Bridging Laboratory Findings To Clinical Applicationsmentioning
confidence: 99%
“…Further studies should be performed to address these issues. LLLT may also selectively inhibit cancer cell proliferation (64) or enhance tumor cell killing with RT (63). This imply that LLLT may have a role as an adjuvant to RT to enhance cancer treatment and be incorporated into the RT treatment plan.…”
Section: Bridging Laboratory Findings To Clinical Applicationsmentioning
confidence: 99%
“…1 It is broadly applied to reduce inflammation, 2 promote tissue regeneration, 3 relieve pain 4 enhance healing process of wound 5,6 and increase cell proliferation. 7,8 The molecular mechanisms of biological responses after LLL exposure have not been fully demonstrated. It is believed that physiological effects induced by LLL depend on the absorption of energy by some molecular photoacceptors or chromophores in the target cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works showed that LLLT can prevent or mitigate the deleterious effects of the ionizing radiation , however, it is unclear whether LLLT could mitigate the damage only in healthy cells or if the laser radiation would also promote tumor cell recovery after IR. Our results showed different behavior of fibroblasts and tumor cells treated with IR followed by LLLT.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, low‐level laser therapy (LLLT) using red and near infrared wavelengths is a non‐ionizing radiation that has been reported to modulate harmful effects of the IR in vitro and in vivo . In fact, in vitro studies show that depending on light parameters and type of cell, pre‐exposure to LLLT can modulate the cytotoxic response of normal and cancer cells to γ radiation . Pre‐clinical and clinical trials report that LLLT following IR is able to reduce cell apoptosis and stimulate revascularization of parotid glands and to improve thyroid and liver functions besides enhancing antioxidant levels and the number of platelets .…”
Section: Introductionmentioning
confidence: 99%